PENEGAKAN HUKUM ATAS KEADILAN DALAM PANDANGAN ISLAM - Ahmad, M. Rais (MIZAN: JOURNAL OF ISLAMIC LAW, 2013)
The human being is a very important factor in achieving legal justice. Legal justice is very coveted by anyone, including offenders though. If in a country that tends to act unjust law, including judges, then the government must act to prevent it. The government should enforce legal justice, not even apply to the unjust people. So that social justice can be created in people’s lives, in addition there is help each other in doing good. There is a sense of interdependence with one another in social life (interdependence).